Migration, Ethnocentrism and Linguistic Diversity Effect in the Development of the Takestan city - Esmaeil Nasiri; Ali Ahmadi; Reza Rahmani (تحقیقات کاربردی علوم جغرافیایی)
Migration is among important issues that less developed and developing countries have confirmed during the recent five decades. This issues in Iran has attraced a lot of researcher and planner views. Irregular and increasing migrations have created a lot of consequences for cities and the target settlements, social effects of migration on the cities is among such consequence these, in this project, ethnocentrism, linguistic diversity and conformance quality are considered among the city's residents. This issue has been studied in Takestan Qazvin. For illustrating the issue, theories of Michael Todaro, Edward Sapir, Benjamin Whorf and William Samner have been used. The research has been done according to library methods (documents) and field methods (special for questionnaires and measurement).In addition to confirming the questionnaire by the experienced faculties, its reliability has been obtained in accordance with Cornbrash’s Alpha coefficient by 82,2 percent and the SPSS software is used for analyzing and processing. The result obtained by analyzing questionnaire filled in by 400 people that the number has been chosen according to Morgan's Table, and the people have been chosen randomly, shows that there is a meaning full relation ship between ethnocentrism and linguistic diversity with development of the city.